Planning and Design Concept Supervision in Reflecting History and Local Culture to a City Corridor as an Effort to Control Spatial Planning - Caesarina, Hanny Maria; Setiawan, Kiky Permana (Comment: an International Journal of Community Development, 2018)
Abstract History and culture always been a part of a city. This community service activity intended to give a supervision about how to reflect history and local culture to a city corridor in the making of planning and design concept in Katingan, Kasongan City of Central Kalimantan. Participants were the government employee of Katingan’s public work and spatial planning services. The tools and materials used in the supervision are a mini portable projector, laptop, and software: Arc GIS 10.4, and Sketch Up. The outcomes of this training activity are the employees can identify, analyze and incorporating history and local culture of a city and produce it into planning and design concept for a city corridor. A draft of planning and design document of Tjilik Riwut Street as a case study was produced during the activity and can be used as references as one of a tool to control spatial planning activity.